Combined Treatment with Micro-Focused Ultrasound with Visualization and Intradermal Incobotulinumtoxin-A for Enlarged Facial Pores: A Retrospective Study in Asians - Park JY; Lee JS; Lee SR; Lee DH (Dove Medical Press, 2023)
Je-Young Park,1,* Ji Su Lee,2,* Soo Ran Lee,2 Dong Hun Lee2- 4 1Apkoo-Jung Oracle Dermatology Center, Seoul, Republic of Korea; 2Department of Dermatology, Seoul National University Hospital, Seoul, Republic of Korea; 3Department of Dermatology, Seoul National University College of Medicine, Seoul, Republic of Korea; 4Institute of Human-Environment Interface Biology, Medical Research Center, Seoul National University, Seoul, Republic of Korea*These authors contributed equally to this workCorrespondence: Dong Hun Lee, Department of Dermatology, Seoul National University Hospital, 101 Daehak-ro, Jongno-gu, Seoul, 03080, Republic of Korea, Tel +82-2-2072-4916, Fax +82-2-742-7344, Email ivymed27@snu.ac.krBackground: Despite the increasing need for the improvement of enlarged facial pores, the treatment remains challenging. A few previous studies have reported the effects of micro-focused ultrasound with visualization (MFU-V) or intradermal incobotulinumtoxin-A (INCO) on enlarged facial pores.Objective: To evaluate the efficacy and safety of combined treatment with superficial MFU-V and intradermal INCO for enlarged facial pores.Methods: This single-center retrospective study included 20 patients treated with MFU-V and intradermal INCO to improve enlarged facial pores. Outcomes were evaluated 1, 4, 12, and 24 weeks after a single session of the combined procedure. Pore count and density were objectively quantitated using a three-dimensional scanner, and improvement was assessed using the physician and patient Global Aesthetic Improvement Scale (GAIS).Results: The mean pore count and density decreased after one week and decreased by up to 62% until 24 weeks. After one week, almost all patients (100% in physician GAIS and 95% in patient GAIS) showed improvement with a grade 3 (much improved) or higher. All adverse events were transient.Conclusion: Combined treatment with MFU-V and intradermal INCO could be effective and safe for reducing enlarged facial pores; the improvements can be sustained for up to 24 weeks.Keywords: pores, enlarged facial pores, incobotulinumtoxin-A, micro-focused ultrasound with visualization